A New Wind Turbine Generating System Model for Balanced and Unbalanced Distribution Systems Load Flow Analysis - Koksoy, Ahmet; Ozturk, Onur; Balci, Murat Erhan; Hocaoglu, Mehmet Hakan (Mdpi, 2018)
Wind turbine generating systems (WTGSs), which are conventionally connected to high voltage transmission networks, have frequently been employed as distributed generation units in today's distribution networks. In practice, the distribution networks always have unbalanced bus voltages and line currents due to uneven distribution of single or double phase loads over three phases and asymmetry of the lines, etc. Accordingly, in this study, for the load flow analysis of the distribution networks, Conventional Fixed speed Induction Generator (CFIG) based WTGS, one of the most widely used WTGS types, is modelled under unbalanced voltage conditions. The Developed model has active and reactive power expressions in terms of induction machine impedance parameters, terminal voltages and input power. The validity of the Developed model is confirmed with the experimental results obtained in a test system. The results of the slip calculation based phase-domain model (SCP Model), which was previously proposed in the literature for CFIG based WTGSs under unbalanced voltages, are also given for the comparison. Finally, the Developed model and the SCP model are implemented in the load flow analysis of the IEEE 34 bus test system with the CFIG based WTGSs and unbalanced loads. Thus, it is clearly pointed out that the results of the load flow analysis implemented with both models are very close to each other, and the Developed model is computationally more efficient than the SCP model.
Keywords: wind energy; induction generators; unbalanced conditions; distribution systems; power flow